PENENTUAN KESESUAIAN LAHAN PERTANIAN TANAMAN CABAI MENGGUNAKAN METODE NAÏVE BAYES DI KABUPATEN KUPANG - Welmy Sinlae; Sebastianus A. S. Mola; Nelci Dessy Rumlaklak (Universitas Nusa Cendana, 2021)
The chili plant is one of the plants cultivated in East Nusa Tenggara (NTT). Kupang Regency is one of the chili producing areas in NTT. Overall chili production in Kupang Regency from 2019 to 2020 has increased. However, the increase in production has not been maximized considering the large amount of land that has not been used as agricultural land. Therefore we need a system that helps in determining the suitability of agricultural land for planting chilies. In this research case-based reasoning (CBR) in determining the suitability of agricultural land for chili plants. The method used in this research is Naïve Bayes with 7 criteria, namely, rainfall, drainage, soil texture, soil depth, C-organic, land slope and the danger of a disaster. The process of finding a solution begins by eliminating irrelevant data using the Naive Bayes method and continues with ranking the best similarity values ​​using KNN. Based on the test results with 110 cases of chili fields, the highest accuracy result is 92.2%, and the average accuracy result of the entire fold is 89.1%.